UNELE ASPECTE CU PRIVIRE LA COMPENSAREA PREJUDICIULUI MORAL CAUZAT SALARIATULUI - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
Unfortunately, petitioners, defendants as well as judicial instances do not give any arguments for their decision of giving a compensation for moral damage and factors that influenced its quantum. The employee can ask for compensation for moral damage any time, when he considers that the employer has caused him moral damage (physical and psychological pain), as well as other rights as the result of neglecting or unsatisfactory execution of the work contract, even if in the contract and in the lab our it is not foreseen.